A RESEARCH TREND: TALENT MANAGEMENT PRACTICE IN HALAL MANAGEMENT - Sharifah Azwani Syed Hamzah; Shazali Johari; Yus Aniza Yusof; Mohd Aswad Ramlan; Putri Umairah Batrisyia Mohd Azmi (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2024)
The abstract highlights the growing significance of integrating talent management practices within Halal management frameworks to ensure compliance with Halal standards and foster sustainable growth in the global Halal industry. Despite limited research, this research utilizes a Systematic Literature Review (SLR) using Scopus to investigate current trends, challenges, and opportunities. Bibliometric analysis and visualization techniques are employed to map the research landscape, identify key contributors, and analyze thematic evolution. Results indicate a growing interest in integrating talent management with Halal principles, emphasizing the need for Islamic ethics, Halal standards, and cultural sensitivities in talent strategies. Emerging themes include Sharia-compliant leadership and ethical recruitment, suggesting areas for further exploration. The research underscores the significance of tailored talent management approaches in Halal-certified organizations to address unique challenges and leverage opportunities for sustainable growth.